2016
DOI: 10.1136/bjsports-2015-095031
|View full text |Cite
|
Sign up to set email alerts
|

Injury risk in runners using standard or motion control shoes: a randomised controlled trial with participant and assessor blinding

Abstract: Background/aimThis randomised controlled trial investigated if the usage of running shoes with a motion control system modifies injury risk in regular leisure-time runners compared to standard shoes, and if this influence depends on foot morphology.MethodsRecreational runners (n=372) were given either the motion control or the standard version of a regular running shoe model and were followed up for 6 months regarding running activity and injury. Foot morphology was analysed using the Foot Posture Index method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 31 publications
1
74
0
5
Order By: Relevance
“…Yet, traditional shoe prescription has not prevented RRIs—consider five quality randomised controlled trials (RCT) and observational cohort studies 1–5. In contrast, a recent investigation6 found that motion control shoes protected against injury in experienced runners who had pronated feet. There are likely important methodological reasons for the discrepancies between these studies, such as differing definitions of RRI and various experience levels among runners.…”
mentioning
confidence: 80%
“…Yet, traditional shoe prescription has not prevented RRIs—consider five quality randomised controlled trials (RCT) and observational cohort studies 1–5. In contrast, a recent investigation6 found that motion control shoes protected against injury in experienced runners who had pronated feet. There are likely important methodological reasons for the discrepancies between these studies, such as differing definitions of RRI and various experience levels among runners.…”
mentioning
confidence: 80%
“…Running shoes 50 with specific design features, such as, increased cushioning, stability and/or control have 51 been constructed to help alleviate the development of running injuries previously linked to 52 risk factors such as high impact forces or excessive pronation (13). Despite the 53 implementation of various features, the incidence of running injuries has not substantially 54 changed (13) and there is often limited or contrasting evidence that running shoes can 55 alleviate a sustained or self-reported injury (10,19,24). This inconclusive evidence does not 56 help to understand the role that running shoes may have on influencing a runner's movement 57 patterns.…”
Section: Introduction 46mentioning
confidence: 99%
“…A Cochrane review 16 found orthotics could play a key role in avoiding stress fractures.Malisouxet al 17 showed that motion control shoes where the midsole hardness is 15% higher than the lateral part reduced running related injuries. In their study 32.4% of participants in the standard shoe group recorded injuries whilst only 17.6% of the participants in the motion control shoe group recorded injuries.…”
Section: Discussionmentioning
confidence: 99%